The growth of reading skills in children with Down Syndrome. - Hulme, C; Goetz, K; Brigstocke, S; Nash, H; Lervåg, A; Snowling, M (2012)
There appears to be a close and probably causal relationship between early variations in phoneme skills and later reading skills in typically developing children, though the pattern in children with Down Syndrome is less clear. We present the results of a 2-year longitudinal study of 49 children with Down Syndrome (DS) and 61 typically developing (TD) control children with similar initial levels of reading skill. Phoneme awareness and vocabulary were strong concurrent predictors of initial levels of reading skill in both groups. However, longitudinally phoneme awareness was a predictor of the growth of reading skills in TD children but not in children with DS. There was a very high degree of longitudinal stability in reading skills in children with DS, and initial levels of reading skills seemed to be highly constrained by general language skills, as indexed by vocabulary knowledge, in this population. We conclude that reading development in children with DS shows similarities and differences to the pattern observed in TD children and that phoneme awareness appears to be a less powerful influence on the development of reading skills in children with DS.